EMOTIONAL STABILITY OF WOMEN IN BUCHI EMECHETA'S THE SLAVE GIRL (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT: In this paper, the slave girl by buchi emecheta uses the theme of slavery to analyze the women's emotional stability. Throughout history, women have often had less career opportunities and legal privileges than men. Wife and mother have traditionally been the most significant roles for women, and they have long been perceived as being very different to males. Pat-riarchal society maintains their rights and existence. Emecheta, the heroine of that novel, describes slavery in Ogbanje Ojebeta. Ojebeta began her life as a slave and carried on in different types of slavery. She was first sold into slavery by his own brother, who needed the money to fund his own selfish demands. She is now the victim of her brother's features. However, despite all the hard work and sometimes harsh treatment, her time as a slave was a time of significant personal growth. She is not permitted to choose what she wants since she is a woman. To avoid the prospect of an arranged marriage, Ojebeta shaves her head. She also asserts her own freedom in selecting her partner of marriage. She has turned into a scapegoat for African patriarchy's schemes. As she repeatedly assumes the roles of daughter, sister, and housemaid or, more accurately, niece, lover, and wife that strongly subordinate her to men, Ojebeta moves from one type of servitude to another.